Event management for the development of multi-agent systems using logic programming - Weinbach, Natalia L. (2004)
In this paper we present an extension of logic programming including events. We will rst describe our proposal for specifying events in a logic program, and then we will present an implementation that uses an interesting communication mechanism called \signals & slots". The idea is to provide the application programmer with a mechanism for handling events. In our design we consider how to de ne an event, how to indicate the occurrence of an event, and how to associate an event with a service predicate or handler.